2019
DOI: 10.1002/hep4.1434
|View full text |Cite
|
Sign up to set email alerts
|

Liver‐Targeted Angiotensin Converting Enzyme 2 Therapy Inhibits Chronic Biliary Fibrosis in Multiple Drug‐Resistant Gene 2‐Knockout Mice

Abstract: There is a large unmet need for effective therapies for cholestatic disorders, including primary sclerosing cholangitis (PSC), a disease that commonly results in liver failure. Angiotensin (Ang) II of the renin Ang system (RAS) is a potent profibrotic peptide, and Ang converting enzyme 2 (ACE2) of the alternate RAS breaks down Ang II to antifibrotic peptide Ang‐(1‐7). In the present study, we investigated long‐term effects of ACE2 delivered by an adeno‐associated viral vector and short‐term effects of Ang‐(1‐7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 38 publications
6
49
0
Order By: Relevance
“…Several studies demonstrated that ACE2, as a receptor for SARS-CoV-2, was expressed in cholangiocytes and hepatocytes. 32,33 Moreover, ACE2 was found to be highly expressed in cholangiocytes, which may be the reason for higher levels of serum ALP being observed among COVID-19 patients. Therefore, this study does not exclude that SARS-CoV-2 evokes LD partially through infecting liver directly.…”
Section: Hepatic Functional Indexes Remain Abnormal 14 Days After Dismentioning
confidence: 98%
“…Several studies demonstrated that ACE2, as a receptor for SARS-CoV-2, was expressed in cholangiocytes and hepatocytes. 32,33 Moreover, ACE2 was found to be highly expressed in cholangiocytes, which may be the reason for higher levels of serum ALP being observed among COVID-19 patients. Therefore, this study does not exclude that SARS-CoV-2 evokes LD partially through infecting liver directly.…”
Section: Hepatic Functional Indexes Remain Abnormal 14 Days After Dismentioning
confidence: 98%
“…In the present study, we found that oxygenation index was negatively associated with AST and LDH among COVID-19 patients, suggesting that respiratory function failure may contribute, at least partially, to SARS-CoV-2-evoked myocardial injury. Increasing data demonstrate that angiotension converting enzyme (ACE)2, as a receptor for SARS-CoV-2, exerts a signi cant role in the pathogenesis of COVID-19 patients [22][23][24]. Recently, a report found that ACE2 was also expressed in cardiocytes [25].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the literature and clinical experience, the pathophysiological mechanisms of the patient reported in the case were speculated as follows. First, in addition to alveolar type 2 cells, cholangiocytes also expressed angiotensin converting enzyme2 (ACE2) [8], and could be targeted by SARS-CoV-2 to cause damage to cholangiocytes and hepatocytes. Second, SARS-CoV-2 activated lymphocytes to proliferate and secrete large amounts of pro-inflammatory cytokines, called "cytokine storm", which could attack the tissue cells to cause liver damage, myocardial injury and kidney failure [9].…”
Section: Discussionmentioning
confidence: 99%